EKSPLORASI KONSEP ETNOMATEMATIKA PADA GERAK TARI TRADISIONAL SUKU LIO - Finsensius Yesekiel Naja; Agustina Mei; Sofia Sa'o (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Culture is something that cannot be avoided in everyday life because culture is a complete and comprehensive unit that applies in a community. This allows mathematical concepts to be embedded in cultural practices. The purpose of this study is to describe the ethnomathematical concepts that exist in each traditional dance movement of the Toja and Wanda of the Lio tribe, Mbuli Village, North Waralau. This study uses a descriptive qualitative research type. The subjects in this study were informants, namely, native speakers who were asked by researchers to talk about mathematical concepts in the art of Toja Wanda dance movements, the instrument of this research was the human instrument, data were analyzed descriptively qualitatively. The results show that one of the Toja dance movements remains in place and one foot moves forward, this motion can form vertical and horizontal lines, in the Wanda dance the men's arms stretch to the side with an upright body, and both hands swing forward and backward. intersecting lines and parallel lines, while in every Toja and Wanda dance movement the hands holding the sash while moving each movement, and the legs moving forward, sideways, and backward, these movements always form angles and triangles. It was concluded that every style of the Toja and Wanda dance movements of the Lio tribe, Wolowuwu Village, Mbuli Village, North Warala has ethnomathematical concepts. including vertical lines, horizontal lines, intersecting lines, acute angles, right angles, obtuse angles, arbitrary triangles, isosceles triangles, equilateral triangles, and right triangles.